Abuse of authority as a ground for liability of bodies and persons performing the functions of business entities (Law and Safety, 2023)
The current state of legal doctrine and court practice on the issues of authority abuse as a ground for liability of bodies and persons performing the functions of business entities has been analysed. Since a business entity forms its own will and implements it through its bodies and persons performing the functions of its agencies, the relevant persons must adhere to the powers defined by law and the charter. If they act beyond their own powers, the will of such a legal entity is distorted and their own will, the will of individuals, takes place.The practice of bringing to justice members of bodies and persons performing the functions of business entities has now been established where such a legal entity is held administratively liable for an administrative offence committed by its authorised person. An example of this is cases involving liability for violations of the requirements of the legislation on the provision and disclosure of information in financial services markets.In general, it should be taken into account that the performance of a specific individual on behalf of a business entity in civil turnover does not change the independent nature of the will, behaviour and responsibility of such a legal entity for its actions in civil relations. It has been argued that, based on the general tenets of civil law, abuse of authority as a ground for liability of bodies and persons performing the functions of business entities has its own specifics of application. This is due not only to the actions (inaction) of such persons, but also to the counterparty’s (third party’s) awareness of the fact that the representatives of such a company act within the scope of their powers.It has been proved that the fact that a body and/or a person performing the functions of a business entity’s body committed unlawful, unfair actions or abused its authority is not the only and sufficient ground for invalidating transactions (agreements) concluded by this body on behalf of a legal entity with third parties. There is a need to prove that the counterparty knew (should have known) that the authority to represent the rights and interests of the business entity was limited by its body or a person performing the functions of such a body.
Keywords: legal entity; business entity; agency, agency member; authority; representation; transaction; contract.